2019
DOI: 10.1002/acn3.749
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of successful endovascular treatment in severe cerebral venous sinus thrombosis

Abstract: Objective The objective of this study was to evaluate the thrombus characteristics affecting the extent of recanalization to identify patients with severe cerebral venous sinus thrombus ( CVT ) more likely to benefit from endovascular therapy. Methods Severe CVT patients scheduled for endovascular treatment were prospectively recruited into the study. Each thrombosed venous segment was evaluated regarding complete or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…DSA is also limited in that it is an invasive test, has a high cost, involves radiation exposure and the use of iodinated contrast, and is contraindicated in patients who are pregnant or have iodine allergies or thyroid disease. HR-MRBTI is not only a qualitative method for evaluating pathological stages of thrombus development, but is also a quantitative way to demonstrate thrombus load ( 13 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…DSA is also limited in that it is an invasive test, has a high cost, involves radiation exposure and the use of iodinated contrast, and is contraindicated in patients who are pregnant or have iodine allergies or thyroid disease. HR-MRBTI is not only a qualitative method for evaluating pathological stages of thrombus development, but is also a quantitative way to demonstrate thrombus load ( 13 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on relevant reports 13,19 and previous studies, [9][10][11] BTI has become an important tool to predict the success of thrombus therapy because changes in the venous thrombus signal can be observed on BTI images. With the rising popularity of MR in major hospitals and the development of MR technology, an increasing number of physicians use MR for preoperative Abbreviations: BTI, black-blood thrombus imaging; CE-MRV, contrast-enhanced MR venography; MR, magnetic resonance.…”
Section: Discussionmentioning
confidence: 99%
“…Despite increased advances in recognition of CVST in recent years, accurate and personalized treatment of CVST remains a di cult task in clinical practice because the thrombus composition changes during CVST progress [3]. Recent reports demonstrated that the outcome of endovascular therapy for patients with CVST is associated with the thrombus stage [4][5][6]. Therapeutic schedules for CVST should be based on correct estimation of the thrombus stage [7][8][9].…”
Section: Introductionmentioning
confidence: 99%